The diagramming dictionary : acomplete reference guide for young writers, aspiring rhetoricians, and anyone else who needs to understand how to diagram English sentences - Otto, Jessica; Bauer, Susan Wise (Well-Trained Mind Press, 2019)
Presents a reference guide to diagramming simple to complex English sentences that describes the rules of diagramming and offers color-coded example diagrams.